“Firewalls” and the Human Rights of Migrants - Gonzalez Morales, Felipe (2024)
The access of migrants to public services such as health, education, the judicial system and others, in addition to their recognition, requires that such services do not share the information about the migratory status of their clients with the enforcement agencies. In this way, migrants will be able to seek the public services without fear of being detained or deported. These prohibitions are called “firewalls” and are based on international human rights standards. Many cities from different countries (the so-called “Sanctuary Cities”) have established “firewalls”, although they are still the exception.